Ormeloxifene versus combined oral contraceptive pills to control blood loss in cases of dysfunctional uterine bleeding - Gupta, Ankita; Raj, Rishika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dysfunctional uterine bleeding is one of the most often encountered gynecologic problems causing anemia, reduced quality of life and unnecessary hysterectomies. A prospective study was conducted on women with DUB to study the effect of ormeloxifene versus combined oral contraceptive pills in controlling blood loss in them. Methods: 100 Women with DUB were enrolled randomly in three groups. After baseline assessment each patient in group A was treated with iron tablets, containing 100 mg elemental iron and folic acid 1.5 mg, for three months and were termed as control group. Group B patients were treated with ormeloxifene in dose of 60 mg twice a week for twelve weeks. Group C patients were treated with combined oral contraceptive pills for twenty- one days starting from third day of their LMP. The treatment was continued for three consecutive cycles. The efficacy of the studied drugs was analyzed by comparing the baseline and post treatment PBAC score, haemoglobin level and endometrial thickness, using appropriate statistical tests. Results: Ormeloxifene was more effective than only iron or combined oral contraceptive therapy in controlling menstrual blood loss (79.11% versus 58.57%). There was a reduction in endometrial thickness in group receiving ormeloxifene as well as in the group receiving combined oral contraceptive pills (p=0.486), however this was statistically not significant. Conclusions: Ormeloxifene was significantly better than combined OCP in reduction of menstrual blood flow in cases of DUB. It has better compliance and marked improvement in subjective symptoms as compared to OCP.